Possibilities of endolaryngeal ultrasonography in the diagnosis of laryngeal tumor pathology - N. A. Daikhes; V. V. Vinogradov; S. S. Reshulsky; M. L. Isaeva; E. B. Fedorova; S. M. Kochieva; R. R. Khabiev; K. V. Mishchenko (Опухоли головы и шеи)
Endoscopic ultrasound is a new technique for diagnosis of precancers and tumors of the larynx. This technique proved its effectiveness in identification of pathologies of the gastrointestinal tract. We have adopted the best practices of our colleagues and used endoscopic ultrasound in diagnosis of squamous cell carcinoma of the larynx.The article describes advantages of endoscopic and ultrasound diagnosis of laryngeal pathology, presents a clinical case of using endoscopic ultrasound.